Eco-benign synthesis of multifunctional silver nanoparticles using leptochloa fusca for enhanced biomedical and catalytic applications - Riaz Ahmad Khan; Hidayat Ullah Khan; Shahnaz; Kamran Tahir; Moamen S Refat; Abdel Majid A Adam; Amnah Mohammed Alsuhaibani (Materials Research Express)
The synthesis of nanomaterials with diverse biomedical and catalytic potentials is crucial in this era of rapidly advancing technology and increasing demand for innovative solutions in medicine and catalysis. The current study explores Leptochloa fusca aqueous extract for the eco-benign and cost-effective green synthesis of multifunctional silver nanoparticles (LF-AgNPs) with enormous potential of biomedical and catalytic applications. The bio-fabricated nanoparticles were characterized employing various analytical techniques including UV–Visible, FTIR, XRD, EDX, SEM and TGA. These analyses confirmed the synthesis, chemical composition, size, morphology, crystalline nature and thermal stability of LF-AgNPs. The surface plasmon resonance of LF-AgNPs was recorded at 432–436 nm and the particle size measured via SEM analysis was noted to be 30 to 200 nm. The synthesized LF-AgNPs were examined for their biomedical and catalytic applications. The binding affinity of LF-AgNPs with ssDNA and BSA was ratified spectroscopically by UV–Visible and FTIR techniques. The hyperchromism observed in the UV–vis absorption spectra, as well as changes in the FTIR spectra of ssDNA and BSA upon interaction with LF-AgNPs, indicate the formation of LF-AgNPs–ssDNA and LF-AgNPs–BSA complexes. This type of binding results in conformational changes in ssDNA and BSA structures and therefore LF-AgNPs hold potential for numerous applications like drug delivery, anticancer agents and receptor targeting. The biosynthesized LF-AgNPs were also found to have effective antioxidant (70%) and H _2 O _2 scavenging (77%) properties. Additionally, the agar well diffusion technique demonstrated efficient antibacterial efficacy for LF-AgNPs against both Gram +ve ( Staphylococcus aureus ) and Gram -ve ( Klebsiella pneumoniae ) strains with ZOI values of 19 ± 0.7 mm and 19 ± 0.5 mm, respectively. LF-AgNPs efficiently catalysed the reduction of methylene blue in less than 9 min, using NaBH _4 as a reducing agent. These findings suggest that LF-AgNPs exhibit significant capability for integration into catalytic process of MB reduction and selected biomedical applications.